Dietary supplementation with an extract of purple corn (Zea mays L) reduces vascular risk and hepatic steatosis in broilers - Saltos, Dalisi (2021)
The aim of this study was to determine the effect of supplementation of increasing doses of a purple corn extract (Zea mays L) in the diet of broilers on the productive performance and lipid metabolism. Two hundred Cobb 500 broilers, unsexed, 28 days old, randomly distributed in four treatments were used: T1 (control), T1, T2 and T2 with 0, 0.05, 0.15 and 0.75% purple corn extract (EMM) as a source of anthocyanins. Productive performance, lipid profile, cardiovascular risk indicators (total cholesterol/high-density lipoprotein cholesterol - TC/HDL-c- and low-density lipoprotein cholesterol/HDL-c - LDL-c/HDL-c), glycemia and hepatic steatosis (HE) were evaluated. Ten male chickens per treatment were slaughtered at 56 days of age. The results were analysed using one-way ANOVA and Dunett's mean test, except for the cardiovascular risk indicator CT/HDL-c (non-parametric Kruskal-Wallis test) and Fisher's exact test to compare the proportions of HE between treatments. control and supplemented with EMM. Final weight was higher in T3 and T4 in relation to T1 (p=0.045), while carcass weight, carcass performance and relative weight of abdominal fat were not different between treatments. There were also no differences between treatments regarding serum concentrations of triacylglycerol (TAG), TC, LDL-c, HDL-c and blood glucose. However, the cardiovascular risk indices CT/HDL-c and LDL-c/HDL-c and the proportion of HE were lower when supplementing with EMM (p<0.05). The results suggest that EMM exerts a protective effect against cardiovascular risk and hepatic steatosis, without affecting the productive performance of the birds.